LINGUISTIC PROJECTIONS OF THE MYTHOLOGICAL PICTURE OF THE WORLD - N.B.Rakhimova (Western European Studies, 2025)
This article explores the relationship between language and mythology, focusing on how mythological worldviews are encoded and reflected in linguistic structures. The study examines the linguistic projections of the mythological picture of the world through the use of metaphor, symbol, archetype, and culturally specific lexical units. Special attention is given to the representation of mythological concepts in Uzbek and other world mythologies, where language serves as a semiotic system that preserves ancient cosmological beliefs
Keywords: mythology; linguistic projection; mythological worldview